2020
DOI: 10.1111/os.12743
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Paravertebral Ossification Progression After Cervical Disc Arthroplasty Based on CT Images: A Long‐term Follow‐up

Abstract: This study focused on the assessment of paravertebral ossification (PO) after cervical disc arthroplasty (CDA) using computed tomography (CT) images. Methods: In this retrospective study, 52 patients (from 2004 to 2010) who received CDA at a single center were included (32 males). Preoperative and follow-up X-ray and CT images of all patients who underwent single-level CDA were collected. PO from the C2/3 to C7/T1 in each patient was graded based on a CT grading system. Each segment was divided into operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In our study, no differences in clinical outcomes were found between patients with and without HO. Consistent with our results, Zeng et al's 23 retrospective study of 52 patients with TDR showed no significant differences between preoperative and the final ROM in patients with low-grade paravertebral ossification. A meta-analysis of 444 patients showed that HO was not associated with clinical outcomes, but high-grade HO had a significantly higher VAS score than low-grade HO group.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, no differences in clinical outcomes were found between patients with and without HO. Consistent with our results, Zeng et al's 23 retrospective study of 52 patients with TDR showed no significant differences between preoperative and the final ROM in patients with low-grade paravertebral ossification. A meta-analysis of 444 patients showed that HO was not associated with clinical outcomes, but high-grade HO had a significantly higher VAS score than low-grade HO group.…”
Section: Discussionsupporting
confidence: 93%
“…Mehren et al 19 also noted this evolution. Grade IV HO rates in CDA patients have been reported in the range of 8% to 33% at 10 years 15,17,19,21,33–35. In a systematic review, Kong et al 35 reported evolving rates of severe HO, from 22.2% at two to five years to 47.5% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…14 The occurrence of heterotopic ossification (HO) was graded according to the McAfee classification system 16 and was divided into low-grade HO (0-II) and high-grade HO (III-IV) based on impaired ROM criteria. 17,18 Anterior bone loss (ABL) was evaluated using Kieser's methods 14,19 (Figure 2). The adjacent segment degeneration (ASDeg) was semi-quantitatively evaluated based on the overall degeneration of height loss (graded from 0 to 4), anterior osteophytes (graded from 0 to 3), and endplate sclerosis (graded from 0 to 2).…”
Section: Data Collectionmentioning
confidence: 99%